VALIDATION OF MORPHOLOGICAL CRITERIA FOR CLONAL IDENTIFICATION IN BUDWOOD GARDENS OF RUBBER TREE (HEVEA BRASILIENSIS MUELL. ARG.) CLONES USING MICROSATELLITE MARKERS - Kouakou, H. Michel; Elabo, A.A. Eliathe; Fofana, I. Jésus; Pokou, N. Désiré; N’guetta, A. Simon-Pierre; Gnagne, Y. Michel; Yapi, A. Freddy; S.D. Martial, Yao; Diarrassouba, Nafan; Obouayeba, Samuel (International Journal of Research -GRANTHAALAYAH, 2022)
The inability of almost all rubber tree nursery growers to distinguish between the different rubber tree clones in a budwood garden (JBG) often leads to clonal mixtures. This makes the application of latex harvesting technology unsuitable, which negatively impacts the yield and / or the economic life of the plantations. To overcome this problem, a clonal identification method based on the use of seven (7) morphological criteria in JBG (budwood garden) was developed. Knowing that the morphological criteria are influenced by the environment, the visual recognition of the plants seems approximate or inefficient. In order to check the effectiveness of the morphological criteria, five (5) rubber tree genotypes from two JBGs (budwood gardens) were characterized both morphologically and by microsatellite markers. Characterization by microsatellites was carried out on twelve (12) loci and involved a sample of 25 individuals per genotype. This first study on the use of microsatellite markers revealed that three (3) microsatellite markers (Hb36, Hb43 and Hb110) best discriminate the genotypes (GT1, PB217, IRCA41, IRCA230 and IRCA331) cultivated in Côte d’Ivoire. It also showed that an individual declared non-compliant by the morphological method has 89% chance of being genetically non-compliant, one could be mistaken by 11% in declaring an individual non-compliant while it is genetically compliant (type I error). In addition, an individual declared compliant by the morphological method has a 76% chance of being genetically non-compliant, one could also be mistaken by 24% in declaring compliant while it is genetically non-compliant (type II error).